Stakeholder perspectives on an integrated package of care for lower limb disorders caused by podoconiosis, lymphatic filariasis or leprosy: A qualitative study. - Bethany Davies; Mersha Kinfe; Oumer Ali; Asrat Mengiste; Abraham Tesfaye; Mossie Tamiru Wondimeneh; Gail Davey; Maya Semrau; EnDPoINT Research Team and Consortium (Public Library of Science (PLoS), 2022)
Background Lower limb disorders including lymphoedema create a huge burden for affected persons in their physical and mental health, as well as socioeconomic and psychosocial consequences for them, their families and communities. As routine health services for the integrated management and prevention of lower limb disorders are still lacking, the 'Excellence in Disability Prevention Integrated across Neglected Tropical Diseases' (EnDPoINT) study was implemented to assess the development and delivery of an integrated package of holistic care-including physical health, mental health and psychosocial care-within routine health services for persons with lower limb disorders caused by podoconiosis, lymphatic filariasis and leprosy. Methodology/principal findings This study was part of the first of three phases within EnDPoINT, involving the development of the integrated care package. Focus group discussions and key informant interviews were undertaken with 34 participants between January-February 2019 in Awi zone, Ethiopia, in order to assess the draft care package's feasibility, acceptability and appropriateness. Persons affected by lower limb disorders such as lymphoedema experience stigma, exclusion from families, communities and work as well as physical and financial hardship. Beliefs in disease causation inhibit affected persons from accessing care. Ignorance was a barrier for health care providers as well as affected persons. Training and education of affected persons, communities and caregivers is important in improving care access. It also requires time, space, materials and financial resources. Both top-down and grass roots input into service development are key, as well as collaboration across stakeholders including charities, community leaders and "expert patients". Conclusions/significance This study highlighted the need for the EnDPoINT integrated care package and provided suggestions for solutions according to its three aspects of integrated care (integration into routine care; integration of mental health and psychosocial care; and integration of care across the three diseases), thereby giving support for its feasibility, acceptability and appropriateness.